2013
DOI: 10.1371/journal.pone.0066543
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Activation in the Central Nervous System of Rats in the Initial Stage of Chronic Kidney Disease-Modulatory Effects of Losartan and Moxonidine

Abstract: The effect of mild chronic renal failure (CRF) induced by 4/6-nephrectomy (4/6NX) on central neuronal activations was investigated by c-Fos immunohistochemistry staining and compared to sham-operated rats. In the 4/6 NX rats also the effect of the angiotensin receptor blocker, losartan, and the central sympatholyticum moxonidine was studied for two months. In serial brain sections Fos-immunoreactive neurons were localized and classified semiquantitatively. In 37 brain areas/nuclei several neurons with differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 94 publications
0
10
0
1
Order By: Relevance
“…Given the feasibility by which stress can be modified in CKD relative to other modifiable risk factors, more investigations are required to characterize the role of stress in driving CVD in CKD patients. Most recently, in 4/6 nephrectomized rats, Palkovits et al [132] demonstrated that CKD elicits high activity in several stressand pain-related brain regions, including the limbic system, hypothalamus, and circumventricular organs [132]. However, it remains to be determined whether stress-mediated activation of these brain regions promotes altered autonomic function in CKD and subsequent cardiovascular complications.…”
Section: Mental Stress In Ckdmentioning
confidence: 99%
“…Given the feasibility by which stress can be modified in CKD relative to other modifiable risk factors, more investigations are required to characterize the role of stress in driving CVD in CKD patients. Most recently, in 4/6 nephrectomized rats, Palkovits et al [132] demonstrated that CKD elicits high activity in several stressand pain-related brain regions, including the limbic system, hypothalamus, and circumventricular organs [132]. However, it remains to be determined whether stress-mediated activation of these brain regions promotes altered autonomic function in CKD and subsequent cardiovascular complications.…”
Section: Mental Stress In Ckdmentioning
confidence: 99%
“…In line with these findings, a recent report has suggested that there is a close cross-talk between the kidney and CNS. Fos-activity of supraoptic and magnocellular PVN neurons is reduced in the chronic renal failure rats (Palkovits et al 2013). The involvement of the PVN in control of the kidney through the release of the antidiuretic hormone has been documented (Krowicki and Kapusta 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic kidney disease is frequently associated with neurological disorders affecting both peripheral and central nervous system resulting in behavioral abnormalities, including mental and cognitive dysfunctions (28)(29)(30). It has been shown that mild CKD may lead to activation of limbic system, central sympathetic, stress-and pain-related brain areas (31). Some CKD-related neurological complications have been attributed to impaired permeability of the blood-brain barrier (22,32,33), neuroinflammation, and oxidative stress (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%